POTENSI DAN OPTIMALISASI PRODUKTIVITAS NIRA NIPAH (Nypa fruticans) DARI METODA PENYADAPAN TRADISONAL KE TEKNOLOGI NON KONVENSIONAL - Hadi, Sopyan; Thamrin, Thamrin; Moersidik, Setyo S.; Bahry, Syaiful (Bumi Lestari; Vol 14 No 2 (2014))
The utilization of non-timber forest products of mangrove palm (Nypa fruticans Wurmb) of sap produced through the process of tapping,  is still made   by the traditional way with the amount of sap production is still small or limited for consumption purposes. Sap which contains sugar has a potency to be fermented  into ethanol which is a source of green energy. The problem is the amount of available sap as raw material obtained by traditional tapping is still limited, therefore, more efforts to increase productivity are needed. The purpose of this study was to explore several methods of tapping palm from traditional way towards  non-conventional technologies. This study used an experimental method examining several factors including 1) Duration of pre-tap (10 days, 20 days, 30 days) 2). Pre-tapping stimulation (without and with stimulation) 3) Type of container (non-vacuum container (traditional), 1.5 L small vacuum container, 2L medium vacuum container  and 20L large vacuum containers). 4) The level of luxuriance palm leaf midrib (not dense 0-2 midrib, less dense 3-4 midrib and dense > 4 midrib). Observed variables are sap volumes include volumes of palm sap/stem, sugar, tapping duration/stem. The result obtained from tapping process on mangrove forest in Lubuk Muda Village, Siak Kecil District, Bengkalis Regency Riau Province showed that optimal productivity were obtained on 1). Pre-tapping stimulation at 30 days. 2) Treatment with pre-tapping stimulation. 3) Harvesting on the medium vacuum container and 4) found in dense leaf midrib.
Keywords: Potency, Nypa sap, Tapping, Productivity, Volume, Sugar Levels and the harvesting duration.